Phase I trial of cyclosporine-induced autologous graft-versus-host disease in patients with multiple myeloma undergoing high-dose chemotherapy with autologous stem-cell rescue - Giralt, S.; Weber, D.; Colome, M.; Dimopoulos, M.; Mehra, R.; Van Besien, K.; Gajewski, J.; Andersson, B.; Khouri, I.; Przepiorka, D.; von Wolff, B.; Delasalle, K.; et al. (Journal of Clinical Oncology, 1997)
Purpose: To determine the feasibility and toxicity of inducing autologous graft-versus-host disease (GVHD) with cyclosporine in patients with multiple myeloma undergoing autologous stem-cell transplantation. Patients and Methods: Fourteen multiple myeloma patients with a median age of 50 years (range, 41 to 63) were enrolled. The median time from diagnosis to transplant was 651 days (range, 229 to 3,353). Ten patients had primary refractory disease, two were in first remission, and two were responsive to salvage therapy. The preparative regimen consisted of thiotepa, busulfan, and cyclophosphamide. Cyclosporine was administered daily for 28 days after the stem-cell infusion, and the dose was adjusted to maintain whole-blood cyclosporine levels between 50 and 150 ng/dL in the first seven patients (low-level group) and between 150 and 300 ng/dL in the other seven patients (high-level group). Results: All patients achieved neutrophil engraftment a median of 11 days after transplant. Four patients developed ≤ grade 2 hepatic toxicity, six developed ≤ grade 2 nephrotoxicity, and four developed reversible cardiac toxicity. Only one treatment-related death occurred. Cyclosporine was withheld in seven patients for a median of 6 days because of renal and/or liver dysfunction. One patient developed clinical skin GVHD, which responded to corticosteroid therapy. Six patients developed histologic evidence of GVHD without clinical signs of GVHD (subclinical GVHD). The incidence of clinical and subclinical GVHD was similar in both cyclosporine groups. Three of 11 patients assessable for response achieved remissions. Three patients experienced disease progression 80, 160, and 354 days after transplant. Ten patients are alive without progression between 56 and 444 days after transplant. Conclusion: Induction of autologous GVHD by post- transplant cyclosporine is feasible and well tolerated in patients with multiple myeloma.